Motif Mahasiswa Dalam Menggunakan Jasa Pembuat Skripsi di Perguruan Tinggi - Wulan Nur Ichwana; Syarbaini Saleh; Yummy Jumiati Marsa (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2022)
This study examines students' motivation to use the thesis service at university. This study uses a descriptive qualitative approach. The first instrument of this research was his 2017 - his 2018 students in two different universities in Medan, North Sumatra, a total of 10 students. As information from observations, interviews and documents to support this research. The data analysis method for this study consisted of three steps using the Miles and Huberman model: data reduction, data presentation, inference, and validation. Based on our findings: 1) Consumers over the age of 20 are made up of different ages and different exact science disciplines. Consumers are students at public, and private universities (2) Factors that motivate students to use the services of a thesis adviser include; a) lack of trust in dealing with thesis supervision, b) lack of communication between lecturers and students, c) cultivated habits that undermine independence in working on a thesis, and d) lack of interest in the subject of the degree program. Lack of information about enough knowledge about it, e) desperation because the title is often rejected by lecturers, f) unprofessional research that affects the delay in the dissertation preparation process.